2010
DOI: 10.1002/cm.20467
|View full text |Cite
|
Sign up to set email alerts
|

Delayed embryonic development and impaired cell growth and survival in Actg1 null mice

Abstract: Actins are among the most highly expressed proteins in eukaryotes and play a central role in nearly all aspects of cell biology. While the intricate process of development undoubtedly requires a properly regulated actin cytoskeleton, little is known about the contributions of different actin isoforms during embryogenesis. Of the six actin isoforms, only the two cytoplasmic actins, β cytoand γ cyto -actin, are ubiquitously expressed. We found that γ cyto -actin null (Actg1 −/− ) mice were fully viable during em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 32 publications
5
101
1
1
Order By: Relevance
“…Previous studies demonstrated that Actg1-/-MEFs were mildly growth impaired due to reduced cell survival. 82 Interestingly, NAM-rGO had no effect on the expression of cytoskeleton genes, whereas GO significantly reduced the expression level of Actr2, Actr3, Tuba1a, and Tuba1b. It indicated that GO resulted in a decrease in cell viability due to the downregulation of cytoskeleton genes.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that Actg1-/-MEFs were mildly growth impaired due to reduced cell survival. 82 Interestingly, NAM-rGO had no effect on the expression of cytoskeleton genes, whereas GO significantly reduced the expression level of Actr2, Actr3, Tuba1a, and Tuba1b. It indicated that GO resulted in a decrease in cell viability due to the downregulation of cytoskeleton genes.…”
Section: Discussionmentioning
confidence: 94%
“…γ cyto -Actin–null MEFs showed mild growth impairment and a small decrease in cell viability but were otherwise comparable to control cells in all other parameters tested (Bunnell and Ervasti, 2010; Bunnell et al , 2011). In contrast, β cyto -actin–knockout MEFs exhibited a wide range of more severe phenotypes (Bunnell et al , 2011).…”
Section: Introductionmentioning
confidence: 83%
“…It would be interesting to see whether any of the vegetative plant actins or the ancestral protist actins can function in animals and suppress the embryo lethal phenotype of mice lacking ACTB (Shawlot et al, 1998;Bunnell et al, 2011) or the delayed embryonic development and poor survival of mice lacking ACTG1 (Bunnell and Ervasti, 2010). Moreover, because the human cytoplasmic actins are functional in Arabidopsis, missense mutations in these human actins that are associated with a large number of diseases, including blindness, deafness, myopathies, immune deficiency, and aberrant kidney function, could be easily tested in this plant model.…”
Section: Discussionmentioning
confidence: 99%